Mesangial cells organize the glomerular capillaries by adhering to the G domain of laminin α5 in the glomerular basement membrane - Kikkawa, Yamato (The Rockefeller University Press, 2003)
In developing glomeruli, laminin α5 replaces laminin α1 in the glomerular basement membrane (GBM) at the capillary loop stage, a transition required for glomerulogenesis. To investigate domain-specific functions of laminin α5 during glomerulogenesis, we produced transgenic mice that express a chimeric laminin composed of laminin α5 domains VI through I fused to the human laminin α1 globular (G) domain, designated Mr51. Transgene-derived protein accumulated in many basement membranes, including the developing GBM. When bred onto the Lama5 −/− background, Mr51 supported GBM formation, preventing the breakdown that normally occurs in Lama5 −/− glomeruli. In addition, podocytes exhibited their typical arrangement in a single cell layer epithelium adjacent to the GBM, but convolution of glomerular capillaries did not occur. Instead, capillaries were distended and exhibited a ballooned appearance, a phenotype similar to that observed in the total absence of mesangial cells. However, here the phenotype could be attributed to the lack of mesangial cell adhesion to the GBM, suggesting that the G domain of laminin α5 is essential for this adhesion. Analysis of an additional chimeric transgene allowed us to narrow the region of the α5 G domain essential for mesangial cell adhesion to α5LG3-5. Finally, in vitro studies showed that integrin α(3)β(1) and the Lutheran glycoprotein mediate adhesion of mesangial cells to laminin α5. Our results elucidate a mechanism whereby mesangial cells organize the glomerular capillaries by adhering to the G domain of laminin α5 in the GBM.